Supervision and Training of Psychotherapists in an Indian Therapeutic Community - Srinath, Usha; Kumar S.K., Vijendra (European Journal for Qualitative Research in Psychotherapy, 2011)
The process of getting therapy supervision while working in a therapeutic community setting with persons suffering from chronic mental illness differ from those working in other clinical settings. In therapeutic communities, the demands on therapists are much more complex, multidimensional and result in significant emotional stress or ‘burn-out syndrome’. For this reason, the therapists need to undergo intensive training, supervision and personal work on a regular basis. The present article applies a descriptive-single case study method, focusing on the process of supervision of psychotherapists in a therapeutic community in India. We explore the process of practical training and supervision of psycho- therapists and describe our approach to developing a budding therapist’s skills and sense of autonomy.